A comparative analysis on english translations of Vietnamese songs: a case study of “Em gai mua” = Phân tích so sánh về dịch bài hát tiếng việt sang tiếng anh: một nghiên cứu về bài hát "Em gái mưa" - Đặng, Thùy Trang (2020)
Due to the prosperous development of the Vietnamese music industry, the demand of Vietnamese-English song translations has sharply increased. However, due to the lack of specialized translators and relevant studies, the number and quality of song translation has been limited. The research aims at figuring out the translation problems of Vietnamese-English song translation by evaluating two popular singable translations of “Em gai mua” and testing the “native-speaker” principle. One translation belongs to Kyo York, a foreigner while the other belongs to Step-up English Center, including mostly Vietnamese teachers. The theoretical framework is based on “Pentathlon Principle” initiated by Low (2005) who is a translator and a musician at the same time. The research has been divided into two different phrases to tackle with two relevant research questions. The survey method has applied to collect the data while the qualitative has been the effective tool of data analysis period. Five native English participants have been asked to take the survey for the purpose of evaluating two translations. Based on the data findings and discussion, the researcher has concluded the translation by Step-up English Center was better at conveying the linguistic and extra-linguistic features compared to that by Kyo York and the “Native-speaker” principle did not worked in the case of translating “Em gai mua”. Besides, the researcher has given some recommendations to the later Vietnamese-English song translators for better quality.